Observational and genetic evidence highlight the association of modifiable risk factors with the incidence and severity of neuroimmunological disorders - Jiang-wei Xia; Jia-jian Li; Yu Qian; Jinmin Han; Ming Lin; Ming-yang Wang; Teng Chen; Guo-liang Chai; Yi-nan Zhao; Jun-wei Hao (Brain, Behavior, & Immunity - Health)
Background: Myasthenia gravis (MG), multiple sclerosis (MS), and neuromyelitis optica spectrum disorders (NMOSD) are a heterogeneous group of rare neuroimmunological disorders whose incidence rates have increased in recent years. The relationships between modifiable risk factors and neuroimmunological disorders are not fully understood. Methods: We utilized multiple logistic regression to estimate the relationships between 38 modifiable risk factors and two neuroimmunological diseases using data from nearly 500,000 individuals in the UK Biobank. Additionally, we applied two-sample Mendelian Randomization (MR) analyses using genetic variants as instrumental variables to investigate the causal relationships of 32 modifiable lifestyle factors with 8 outcomes, representing risk and severity across three neuroimmunological diseases. To further explore the underlying mechanisms, mediation analysis was conducted to elucidate how significant associations might be mediated by intermediate variables. Results: Our observational and MR analyses consistently found significant associations (P < 0.05) indicating the number of cigarettes smoked daily, television watching, waist circumference, and BMI are all positively associated with the risk of developing MG. In contrast, moderate-to-vigorous physical activity and higher vitamin D levels are associated with a reduced risk of MS. Moreover, we discovered that the impact of television watching on the risk of MG was mediated by BMI (observational mediation analysis: 26.22%; MR mediation analysis: 9.90%). Conclusions: These findings underscore the importance of modifiable risk factors in the development of neuroimmune diseases and support the identification of personalized intervention and prevention strategies. Notably, BMI significantly mediates the relationship between television watching and MG, indicating potential for targeted interventions to mitigate the risk of MG.